APPLICATION OF TOTAL QUALITY MANAGEMENT IN ISLAMIC EDUCATION: A Case Study of Madrasah Aliyah (MA) Al-Hikmah, Karangmojo, Gunung Kidul, Yogyakarta - Siska Sulistyorini (EL-TARBAWI, 2015)
This paper examines how Total Quality Management in Islamic School can fulfill market demands of quality graduates using Madrasah Aliyah (MA) Al-Hikmah Karangmojo Gunung Kidul Yogyakarta as a case study. Based on the research’s findings, it will show that: (1) in terms of service management, MA al-Hikmah provides service to the customers –the students- by not charging them any fees for educational operational costs, accommodation, health assurance, and educational facilities such as books and courses; (2) in terms of educational process management, MA Al-Hikmah’s teachers teach students using various teaching methods and strategies. Teaching processes are conducted both indoor and outdoor. MA Al-Hikmah also has a teaching team to handle the 12th graders in  extra classes so that they can pass the national examination; (3) in terms of product management, MA Al-Hikmah continuously improves its educational quality through a variety of ways. MA Al-Hikmah also has a special team to maintain students’ achievements morally and academically. MA Al-Hikmah also makes some efforts to provide its graduates with opportunities to get scholarships in the higher education and job vacancies to meet the market needs of quality graduates.